Índice de potencialidade de ocorrência de cavidades em arenitos na Bacia Hidrográfica Tocantins/Araguaia no Estado do Maranhão - Silva, Janderson Rocha (2022)
Geographic Information Systems - GIS has helped in the advancement of several sciences, in Speleology, a science that studies natural cavities and their different approaches, GIS's help in the spatialization of variables that facilitate the location and prospecting of these caves. Based on an approach to the application of Geographic Information Systems, using quantitative methods of multifactor analysis and map algebra, on a scale of 1:100,000, guided by the concept of landscape and the conception of karst in sandstone, the cutout chosen for this study ' was the Tocantins/Araguaia Basin, located in the southwest region of Maranhão. The general objective of the research is to develop a cave occurrence indicator applicable in the Tocantins/Araguaia Basin in the State of Maranhão, through the use of multicriteria analysis. Its specific objectives are to support the validation of the cavities index model and to survey and register the caves found, in addition to briefly characterizing each one of them by their geology, speleogenesis and existence of biological and archaeological resources, if any. Among the factors that guide the need for this study is the location of the Hydrographic Basin, as there are two speleological provinces both on the Maranhão side and on the Tocantins side. Another important factor is present in Decree No. 6640 of 2008, which deals with the need for environmental licensing of the Brazilian speleological heritage, in addition to the geological and morphological characteristics of the area that contribute to the formation of caves in the region. For this, it was decided to use the AHP method (Analyse Hierarchy Processing), which is one of the most used decision-making methods for individual correlation of variables, and to present the result in addition to the numerical way, map algebra will be used. The results showed that the methodology was efficient to measure the potential occurrence of cavities in sandstone, since the average of the cavities found in the prospecting works are located in areas of High and Very High Potentiality for the Tocantins/Araguaia Hydrographic Basin, in addition to the realization of the topographies and registration of the caves with the Brazilian Society of Speleology